l-Ascorbic acid biosynthesis - Smirnoff, Nicholas (Cofactor Biosynthesis: a Mechanistic Perspective, 2001)
Biosynthesis of l-ascorbate (vitamin C) occurs by different pathways in plants and mammals. Yeast contain d-erythroascorbate, a C 5 analog of ascorbate. UDP- d-glucuronic acid is the precursor in mammals. Loss of UDP forms glucuronic acid/glucuronolactone. Reduction of these at C-1 then forms l-gulonic acid/ l-gulono-1,4-lactone. The lactone is oxidized by a microsomal l-gulono-1,4-lactone oxidase to ascorbate. Only the l-gulono-1,4-lactone oxidase has been purified and cloned, and very little is known about the properties of the other enzymes. Plants form ascorbate from GDP- d-mannose via GDP- l-galactose, l-galactose, and l-galactono-1,4-lac-tone. The final oxidation of l-galactono-1,4-lactone to ascorbate is catalyzed by a mitochondrial l-galactono-1,4-lactone dehydrogenase located on the inner membrane and using cytochrome c as electron acceptor. GDP-mannose pyrophosphorylase and l-galactono-1,4-lactone dehydrogenase have been cloned. Yeast synthesizes d-erythroascorbate from d-arabinose and d-arabinono-1,4-lactone in a pathway analogous to that in plants. The plant, mammalian, and yeast aldonolactone oxidase/dehydrogenates that catalyze the last step in each pathway have significant sequence homology. l-Gulono-1,4-lactone oxidase is mutated and not expressed in animals, such as primates, that have lost ascorbate biosynthesis capacity. Assessment of the literature reveals that little is known about many of the enzymes involved in ascorbate biosynthesis or about the factors controlling flux through the pathways. There is also a possibility that minor alternative pathways exist in plants and mammals.